تقصي انتشار بعض الفيروسات التي تصيب محصول البندورة داخل البيوت المحمية في الساحل السوري - عاقل, إنصاف; إسماعيل, عماد; علي, إشراق; الإبراهيم, وطفة (Latakia University Journal -Biological Sciences Series, 2019)
أجري مسح حقلي في موسم 2006- 2007 بهدف تقدير نسبة انتشار ثمانية فيروسات تصيب محصول البندورة داخل البيوت المحمية، جمعت خلاله 580 عينة نباتية أظهرت أعراضاً شبيهة بالفيروسية كالموزاييك، شفافية العروق، التبرقش، الاصفرار، تقزم وتشوه الأوراق. اعتمد في التشخيص اختبار الإدمصاص المناعي المرتبط بالأنزيم بطريقة DAS-ELISA، باستخدام الأجسام المضادة المتعددة الكلونات. بينت النتائج إصابة محصول البندورة طبيعياً بأربعة فيروسات من الفيروسات المختبرة وهي: التبقع الحلقي في البندورةToRSV ، موزاييك التبغTMV ، واي البطاطا PVY، الذبول التبقعي في البندورة TSWV، وبلغت نسبة الإصابات المفردة 2.58 % ، +-2.24%، 1.89%، 0.86% على التوالي، وذلك من أصل 580 عينة مختبرة. وعدم وجود أية إصابة بالفيروسات موزاييك الخيار CMV، تجعد واصفرار أوراق البندورة TYLCV ، موزاييك البندورة ToMV، و فيروس موزاييك بيبينو Pep MV. The aim of this research was to evaluate the percentage of viral infection on Tomato (Lycopersicum esculentum) in Syrian costal region during 2006/2007 growing seasons. Five hundred and eighteen samples with virus suggestive symptoms; mosaic, vein-clearing, , mottle, yellowing, stunting, and leaf distortion were collected and tested by Enzyme Linked Immune Sorbent Assay (DAS-ELISA). Results of DAS-ELISA of tested samples showed the natural infection of tomato crop by Tomato ring spot virus (ToRSV), Tobacco mosaic virus (TMV), Potato Y virus (PVY) and Tomato Spotted wilt virus (TSWV), in Syrian Coast in the following ratios: 2.58%, 2.24%, 1.89%, and 0.86 % respectively, and no positive reaction by Cucumber mosaic virus (CMV), Tomato yellow leaf curl virus (TYLCV), Tomato mosaic virus (ToMV), Pepeno mosaic virus (PepMV).